COVID-19 enters the expanding network of apolipoprotein E4-related pathologies - Gkouskou, K.; Vasilogiannakopoulou, T.; Andreakos, E.; Davanos, N.; Gazouli, M.; Sanoudou, D.; Eliopoulos, A. G. (Redox BiolRedox BiolRedox Biol, 2021)
COVID-19 incidence and case fatality rates (CFR) differ among ethnicities, stimulating efforts to pinpoint genetic factors that could explain these phenomena. In this regard, the multiallelic apolipoprotein E (APOE) gene has recently been interrogated in the UK biobank cohort, demonstrating associations of the APOE epsilon4/epsilon4 genotype with COVID-19 severity and mortality. The frequency of the epsilon4 allele and thus the distribution of APOE epsilon4/epsilon4 genotype may differ among populations. We have assessed APOE genotypes in 1638 Greek individuals, based on haplotypes derived from SNP rs7412 and rs429358 and found reduced frequency of epsilon4/epsilon4 compared to the British cohort. Herein we discuss this finding in relation to CFR and hypothesize on the potential mechanisms linking APOE epsilon4/epsilon4 to severe COVID-19. We postulate that the metabolic deregulation ensued by APOE4, manifested by elevated cholesterol and oxidized lipoprotein levels, may be central to heightened pneumocyte susceptibility to infection and to exaggerated lung inflammation associated with the epsilon4/epsilon4 genotype. We also discuss putative dietary and pharmacological approaches for the prevention and management of COVID-19 in APOE epsilon4/epsilon4 individuals.
Keywords: *Apolipoprotein E4/genetics; *Covid-19; Alleles; Apolipoproteins E/genetics; Genotype; Humans; SARS-CoV-2